Design and implementation of a COTS-based flight computer - McDowell, Kyle (Kansas State University, 2005)
Instead of designing new proprietary hardware to replace aging, obsolete systems, the defense industry is looking towards Components Off The Shelf (COTS). COTS are attractive for a number of reasons. First, by using COTS, nonrecurring design costs are divided among all costumers. Second, because COTS suppliers have an economy of scale, the suppliers are able to reduce the cost of components, making systems more affordable than low-volume, proprietary solutions. Third, using COTS accelerates the time to market by reducing the time required for design and making extensive design verification unnecessary. Fourth, COTS hardware produces a scalable solution, as one COTS systems could easily be replaced with a different COTS system that would more readily meet the customer's unique demands. This thesis attempts to explain the implementation of a COTS-based flight computer. The PCI Mezzanine Card (PMC) standard has been selected because it is both rugged and widely accepted by industry. The PMC is a common standard with a variety of COTS parts, making it easily exchangeable. While the COTS solution reduces design overhead, it does not eliminate the need for design altogether. Although the contractor would no longer be required to design the features provided by the COTS, they would be required to design the overall system and the integration of the COTS. This thesis documents the design of a system that takes two PMC cards – the COTS – and integrates those cards together and interfaces them with the flight systems. The interfacing of COTS components is also extended to provide a high-speed serial link in order to connect two PMC carrier boards for a total of four COTS PMCs. Further, the testability of the final system is explored to provide an end product that is verifiably sufficient.
Keywords: Commercial off the shelf; Electrical engineering; Engineering, Electronics and Electrical (0544)